Catalytic Enantioselective 1,3-Dipolar Cycloadditions of Azomethine Ylides for Biology-Oriented Synthesis - Narayan, Rishikesh (American Chemical Society, 2014)
[Image: see text] Cycloaddition reactions are among the most powerful methods for the synthesis of complex compounds. In particular, the development and application of the 1,3-dipolar cycloaddition, an important member of this reaction class, has grown immensely due to its powerful ability to efficiently build various five-membered heterocycles. Azomethine ylides are commonly used as dipoles for the synthesis of the pyrrolidine scaffold, which is an important motif in natural products, pharmaceuticals, and biological probes. The reaction between azomethine ylides and cyclic dipolarophiles allows access to polycyclic products with considerable complexity. The extensive application of the 1,3-dipolar cycloaddition is based on the fact that the desired products can be obtained with high yield in a regio- and stereocontrolled manner. The most attractive feature of the 1,3-dipolar cycloaddition of azomethine ylides is the possibility to generate pyrrolidines with multiple stereocenters in a single step. The development of enantioselective cycloadditions became a subject of intensive and impressive studies in recent years. Among many modes of stereoinduction, the application of chiral metal–ligand complexes has emerged as the most viable option for control of enantioselectivity. In chemical biology research based on the principle of biology-oriented synthesis (BIOS), compound collections are prepared inspired by natural product scaffolds. In BIOS, biological relevance is employed as the key criterion to generate hypotheses for the design and synthesis of focused compound libraries. In particular, the underlying scaffolds of natural product classes provide inspiration for BIOS because they define the areas of chemical space explored by nature, and therefore, they can be regarded as “privileged”. The scaffolds of natural products are frequently complex and rich in stereocenters, which necessitates the development of efficient enantioselective methodologies. This Account highlights examples, mostly from our work, of the application of 1,3-dipolar cycloaddition reactions of azomethine ylides for the catalytic enantioselective synthesis of complex products. We successfully applied the 1,3-dipolar cycloaddition in the synthesis of spiro-compounds such as spirooxindoles, for kinetic resolution of racemic compounds in the synthesis of an iridoid inspired compound collection and in the synthesis of a nitrogen-bridged bicyclic tropane scaffold by application of 1,3-fused azomethine ylides. Furthermore, we performed the synthesis of complex molecules with eight stereocenters using tandem cycloadditions. In a programmable sequential double cycloaddition, we demonstrated the synthesis of both enantiomers of complex products by simple changes in the order of addition of chemicals. Complex products were obtained using enantioselective higher order [6 + 3] cycloaddition of azomethine ylides with fulvenes followed by Diels–Alder reaction. The bioactivity of these compound collections is also discussed.